Redescription and notes on the ecology of Pagurapseudes dentatus (Brown, 1956) (Peracarida: Tanaidacea), a shell-inhabiting tanaid from South Africa. Issue 6 (24th September 2020) - Brokensha, Rouane; Landschoff, Jannes; du Plessis, Anton; Griffiths, Charles L
Abstract: The tanaid Pagurapseudes dentatus was described from a male collected from the intertidal zone at False Bay, South Africa. The description was poorly illustrated, incomplete, did not describe the female or juvenile stages, and gave no information on its habitat. The species was rediscovered and found to be locally abundant at locations in South Africa, where it inhabits vacant gastropod shells. We redescribe P. dentatus by fully illustrating and describing its morphological characters, including the copulatory female and manca II stages. Pagurapseudes dentatus differs from similar species by a long seta on the basis of the characteristically elongated pereopod-1, as well as its singular distal pectinate setae on the propodus and adjacent to the dactylus of pereopod 6. Nano-CT scanning was used to illustrate and document the unusual mode of occupation of empty gastropod shells by the species. It was found ( N = 139) occupying shells of 19 gastropod species from 10 different genera, occurring most abundantly in shells of Tricolia Risso, 1826, Burnupena Iredale, 1918, Assiminea Fleming, 1828, and Gibbula Risso, 1826. It forms dense populations under intertidal boulders, where it co-occurs with, and may compete for empty shells, with at least two common species of hermit crabs.